Exploring the Effect of AI Trust on Firm Creativity to Generate Performance at AI-Ready Firms - Puteri Rozyanti, Amanda; Pramesti Cahyani, Diah; Kinanti, Lintang; Maharani, Anita (IPB University, 2024)
Artificial Intelligence (AI) is increasingly popular to be provided by firms to support the work of employees. This study aims to establish the circumstances under which AI can bring organizational value to firms which analyzes the concept of AI Capabilities to increase Firm Creativity and Firm Performance while also discovering the extent to which AI Trust plays a role in generating creativity. Primary data was collected from 61 respondents, analyzed using PLS-SEM to discover the relationship between variables. Highlighting the moderating effect of AI Trust between AI Capabilities and Firm Creativity within Indonesian firms, this study found that AI Capabilities themselves are more significant in building upon creativity, although trust is not embedded to generate performance. Such a finding provides a critical point whereby trust should be channeled towards ensuring its ethical and responsible utilization rather than being used as a mechanism to curtail AI's ability to stimulate creativity. While AI-ready firms are still very limited in Indonesia, this study suggests more firms start facilitating employees with AI to support their work by not only enhancing the capabilities but also sharing knowledge in a systematic, incremental, and iterative manner to generate the same understanding and ethics on how to collaborate with AI at work.